Zootechnical and economic performance indexes of dairy herds with different production scales - De Andrade Ferrazza, Rodrigo [UNESP]; Lopes, Marcos Aurélio; Bruhn, Fabio Raphael Pascoti; De Moraes, Flavio (Universidade Estadual de Londrina, 2018)
This study aims to estimate the zootechnical and economic benchmarks of milk production systems, analyze production scale effects on dairy farming returns, and identify the system components that best represent the total and effective operational costs. We analyzed 22 size, zootechnical and economic performance indexes from 61 dairy farms located in Minas Gerais state, Brazil. The sample of herds were clustered according to three production strata. The results were compared using analysis of variance (normal distribution) and Kruskal-Wallis (non-normal distribution) tests, and post-hoc comparisons were undertaken with Fisher’s least significant difference test. The relationship between some variables was tested using the Pearson correlation test. The production scale was best defined by the number of lactating cows (r=0.96) in comparison to the area (r=0.83). The production scale proved to be a suitable criterion for the analyses between different groups of producers, and it is more easily obtained and probably provides more accurate results. The milk production systems studied presented higher zootechnical indexes than those found in average of Brazilian farms, but lower than international indices or technologically advanced farms from other Brazilian regions. A greater production scale is a desirable condition, although it failed to ensure the economic efficiency of the herds studied. The components of total and effective operating costs that had the greatest representativeness were, in descending order, food and labor.
Keywords: Benchmark; Dairy cattle; Production cost; Profitability; Stratification criterion